1980
DOI: 10.1021/bi00546a005
|View full text |Cite
|
Sign up to set email alerts
|

Translation of chick aortic elastin messenger ribonucleic acid. Comparison to elastin synthesis in chick aorta organ culture

Abstract: Studies were undertaken to define the molecular size of the elastin primary gene product. Translation of chick aortic messenger ribonucleic acid (mRNA) in an mRNA-dependent reticulocyte lysate resulted in the synthesis of two major proteins of 70 000 and 73 000 molecular weights. Both proteins were shown to be soluble forms of elastin by isotope incorporation, immunoprecipitation, collagenase and cyanogen bromide sensitivity, and two-dimensional gel electrophoresis. The 70 000-dalton protein behaves similarly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
30
0

Year Published

1981
1981
1997
1997

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(34 citation statements)
references
References 35 publications
4
30
0
Order By: Relevance
“…This yields an average mRNA length of about 1,500 nucleotides which is in agreement with the average size determined for cotton cotyledons by other means (10,14,29). Since (9) and the antigen and antibody solubilized by incubation at 37 C in Laemmli sample buffer (19) for 30 min. Aliquots of the supernatant from this solubilization step were applied to the ID gel without further treatment.…”
Section: Methodssupporting
confidence: 88%
See 1 more Smart Citation
“…This yields an average mRNA length of about 1,500 nucleotides which is in agreement with the average size determined for cotton cotyledons by other means (10,14,29). Since (9) and the antigen and antibody solubilized by incubation at 37 C in Laemmli sample buffer (19) for 30 min. Aliquots of the supernatant from this solubilization step were applied to the ID gel without further treatment.…”
Section: Methodssupporting
confidence: 88%
“…If the translation mixture is first treated with TCA or acetone to precipitate protein and then antibodies added to the solubilized precipitate after the manner of Chua (3) and many others, the 69-and 50-kD translation products are immunoprecipitable in good yield, whereas only traces of the 60-kD protein can be precipitated. This phenomenon in which antibodies to mature proteins react poorly with initial translation products that are destined to undergo extensive modification is not unusual (9) and has been found in the case of storage proteins of peas (16).…”
Section: Synthesis Of Storage Proteinsmentioning
confidence: 71%
“…It has been suggested (Foster et al, 1980Barrineau et al, 1981) that two elastin gene products are differentially expressed during chick development. Furthermore, the translation product of mRNAE from sheep nuchal ligament can produce a doublet on NaDodSO4/polyacrylamide-gel electrophoresis .…”
Section: Discussionmentioning
confidence: 99%
“…M. Davidson and others 1979;Foster et al, 1980Foster et al, , 1981Burnett et al, 1980Burnett et al, , 1981Burnett et al, , 1982Davidson et al, 1981Shibahara et al, 1981; levels, make it clear that it is important to understand the structure and function of elastin genes, especially since many of these studies have suggested that elastin-gene expression is likely controlled at the transcriptional level.…”
mentioning
confidence: 99%
“…Total mouse liver RNA isolated by centrifugation through CsCl (Foster et al, 1980) was translated in nuclease-treated rabbit reticulocyte lysate as per the manufacturer's instructions. After translation, radiolabelled proteins were either immunoprecipitated as described above after the addition of 5 vol.…”
Section: Translation and Processingmentioning
confidence: 99%